2014
DOI: 10.1186/1756-3305-7-85
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of fluralaner in dogs following a single oral or intravenous administration

Abstract: BackgroundFluralaner is a novel systemic insecticide and acaricide. The purpose of these studies was to investigate the pharmacokinetic properties of fluralaner in Beagle dogs following single oral or intravenous (i.v.) administration.MethodsFollowing the oral administration of 12.5, 25 or 50 mg fluralaner/kg body weight (BW), formulated as chewable tablets or i.v. administration of 12.5 mg fluralaner/kg BW, formulated as i.v. solution to 24 Beagles, plasma samples were collected until 112 days after treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 8 publications
6
93
2
1
Order By: Relevance
“…A 2012 compilation considering the chronology and numbers for introduction of the current insecticides gave the GABA-R targeting compounds as only 1.7% of the total with half of them introduced by 1955 [81]. Newly introduced GABAergic insecticides are flu and afoxolaner used for flea and tick control on cats and dogs [58,[62][63][64][65]. There are also important crop pests highly sensitive to NCA-IIs [24,60,82] indicating possible expanded use on optimization.…”
Section: Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2012 compilation considering the chronology and numbers for introduction of the current insecticides gave the GABA-R targeting compounds as only 1.7% of the total with half of them introduced by 1955 [81]. Newly introduced GABAergic insecticides are flu and afoxolaner used for flea and tick control on cats and dogs [58,[62][63][64][65]. There are also important crop pests highly sensitive to NCA-IIs [24,60,82] indicating possible expanded use on optimization.…”
Section: Prospectsmentioning
confidence: 99%
“…Several types of evidence establish that isoxazolines [57][58][59][60][61][62][63][64][65][66] and meta-diamides (including mDA-7 [24,67] and BPB-1 [68]) are NCAs but at a different high affinity site(s) than those for compounds acting at the NCA-IA, NCA-IB and AVE targets ( …”
Section: Nca Actionmentioning
confidence: 99%
“…Clinical trials have demonstrated the ectoparasitic efficacy of fluralaner as a gamma-aminobutyric acid (GABA) and glutamategated chloride channel inhibitor with potent selectivity for arthropod neuron receptors, resulting in excess neuronal stimulation and rapid insect death after feeding exposure [9,10]. After oral ingestion by the dog, fluralaner is rapidly absorbed and widely distributed, with a long half-life of 12-15 days.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical observations were scheduled to cover the period of highest systemic exposure to milbemycin oxime, praziquantel [2,3] and fluralaner [6]. Therefore, clinical signs associated with the concurrent use, e.g.…”
Section: Resultsmentioning
confidence: 99%